A multimodal literary analysis of a television commercial - Melissa Shamini Periasamy; Gruba, Paul; Ganakumaran Subramaniam (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
Literature and advertisements are analogous in the way they mimic the surrounding culture, art and practices and in their ability to elicit various emotional responses in people. Over the years, literature has had a great influence in advertisements and much of advertisement content has used poetic verses, prose forms and dramatic elements. Television commercials largely draw inspiration from drama in the construction of the advertisers’ messages. As a multimodal text, a television commercial (TVC) utilises multiple modes of meaning to employ literary elements in its content. Based on the view of TVCs as literary texts, this paper examines the literary elements of setting and character in a TVC through multimodal analysis. The multimodal elements that construct setting and character in a corporate TVC are identified and analysed. In line with multimodal analysis, the meanings of the modes are discussed by taking into account the socio-cultural context in which the TVC is produced and viewed. In doing so, the significant role of setting and character in meaning making of a TVC is revealed. This paper demonstrates the application of the multimodal approach to analysis of literary elements in a TVC and subsequently contributes to developing and promoting applications of multimodal analytical approaches in literary studies.